Multidimensional MRI-CT atlas of the naked mole-rat brain - Seki, Fumiko; Hikishima, Keigo; Nambu, Sanae; Okanoya, Kazuo; Okano, Hirotaka J.; Sasaki, Erika; Miura, Kyoko; Okano, Hideyuki (Frontiers in Neuroanatomy, 2013)
Naked mole-rats have a variety of distinctive features such as the organisation of a hierarchical society (known as eusociality), extraordinary longevity, and cancer resistance; thus, it would be worthwhile investigating these animals in detail. One important task is the preparation of a brain atlas database that provide comprehensive information containing multidimensional data with various image contrasts, which can be achievable using a magnetic resonance imaging (MRI). Advanced MRI techniques such as diffusion tensor imaging (DTI), which generates high contrast images of fibre structures, can characterise unique morphological properties in addition to conventional MRI. To obtain high spatial resolution images, MR histology, DTI, and X-ray computed tomography (CT) were performed on the fixed adult brain. Skull and brain structures were segmented as well as reconstructed in stereotaxic coordinates. Data were also acquired for the neonatal brain to allow developmental changes to be observed. Moreover, in vivo imaging of naked mole-rats was established as an evaluation tool of live animals. The data obtained comprised three-dimensional (3D) images with high tissue contrast as well as stereotaxic coordinates. Developmental differences in the visual system were highlighted in particular by DTI. Although it was difficult to delineate optic nerves in the mature adult brain, parts of them could be distinguished in the immature neonatal brain. From observation of cortical thickness, possibility of high somatosensory system development replaced to the visual system was indicated. 3D visualisation of brain structures in the atlas as well as the establishment of in vivo imaging would promote neuroimaging researches towards detection of novel characteristics of eusocial naked mole-rats.